'A Day for Pierre Boulez', Lucerne Festival im Sommer, Kultur- und Kongresszentrum. (7th December 2015) - Adler-McKean, Jack
Abstract : The ninetieth birthday of the last surviving founding father of post-WWII classical music is certainly reason enough for celebration, but what could the Lucerne Festival offer that has not already been covered by the many festivities that have taken place around the world? Fortunately, the festival has a trump card up its sleeve: the Lucerne Festival Academy, founded 11 years ago by Pierre Boulez and festival director Michael Haefliger to provide young musicians with the opportunity for intensive study of the music of the twentieth and twenty-first centuries. The Lucerne Festival Academy Orchestra and Ensemble were omnipresent during 11 concerts given over nine hours on 23 August 2015, performing eight world premieres from three generations of composers inspired by Boulez, alongside eight works from the master himself.